THE CONTROLLING FACTOR OF SEASONAL VARIABILITY OF STABLE WATER VAPOR ISOTOPE ABUNDANCE IN THE ATMOSPHERE OF MARITIME CONTINENT - Triyono
Stable water vapor isotopes (HDO) are known to have large spatial and temporal variability and can respond to seasonal variability in atmospheric circulation. The Indonesian maritime continent is known to have seasonal variations in atmospheric circulation, most of which have peaks on the DJF and JJA. Thus, a study about controlling factor that affects seasonal abundance of HDO in the Indonesian maritime continental region is conducted. Seasonal HDO variation is seen from the distribution anomalies in the two seasons of DJF and JJA. The HDO concentration then correlated with the forcing variable in the Isotopic Circulation Model (ICM) to see its effect on the seasonal concentration of HDO. The variables correlated with the concentration of HDO include evaporation, precipitation, and precipitable water, and compared visually with moisture transport. Based on the results of data processing and analysis, it was found that precipitation and moisture transport had an effect on seasonal variations of HDO in several regions of the Indonesian maritime continent both at the DJF and JJA. Whereas evaporation is seen in almost all regions of Indonesian maritime contonent in JJA. But there are still a number of anomalous areas that cannot be explained by the influence of the variables above.